"Propalladia" and other works of Bartolomé de Torres Naharro, edited by Joseph E. Gillet. Vol. III, Notes. Bryn Mawr, Pennsylvania, 1951. viii + 892 págs. - Weber de Kurlat, Frida (Nueva Revista de Filología Hispánica (NRFH), 1952)
Se reseñó el libro: "Propalladia" and other works of Bartolomé de Torres Naharro, edited by Joseph E. Gillet. Vol. III, Notes.